The Challenge of the Mosaic Torah in Judaism, Christianity, and Islam - Laato, Antti, (Studies on the Children of Abraham ;, 2021)
The aim of The Challenge of the Mosaic Torah in Judaism, Christianity, and Islam is to address the theological issues arising when different ancient religious groups inside three Abrahamic religions attempted to understand or define their opinion on the Mosaic Torah. Twelve articles explore various instances of accepting, modifying, ignoring, criticizing, and vilifying the Mosaic Torah. They demonstrate a range of perspectives of ways in which the Mosaic Torah has formed a challenge. These challenges include Persian religious policy (when the Mosaic Torah was formed), intra-Jewish discussions (e.g. Samaritans), religious practices (the New Testament debates of ritual laws) and interreligious debates on validity of the Torah stipulations (with Christians and Muslims). All the papers were discussed at the international conference, "The Challenge of the Mosaic Torah in Judaism, Christianity and Islam", organized by Åbo Akademi University and held in Karkku, Finland, 17-18 August, 2017.